The Study of the Elderly Accidents in Kerman Province on 2006-9 - Hossein Safizadeh; Hamideh Habibi; Ruhollah Zahmatkesh; Mohamad Samery (University of Social Welfare & Rehabilitation Sciences, 2013)
Objectives: The elders just like the other age groups can be injured or dead in the cause of accident although because of their physical conditions and their age they got a little attention and care. The aim of this study was description of elderly trauma in Kerman province. Methods & Materials: The study was designed as a cross sectional and it examines 11120 persons that are 60 years old and above from 282618 traumatic cases registered in 2006-2009 in Kerman province (except Rafsanjan city). Data were analyzed using t-Test and Chi-Square. Results: From all the examined persons 63% belongs to male and 37% belongs to female. The mean age of examined persons is 69.05(±7.97) years old.The most common trauma belonged to traffic accidents (25.3%) then it comes to Trauma (18.6%) and fall (11.1%). Most of the accidents happened in home (41.7%), alleys and streets (30.2%) in the second place .From all of the injured cases, 91 of them (0.82%) are dead. Data assessment indicates that the injured females were elder than males (P<0.05), the dead injured also elder from alive persons (P<0.01). The most common cause of the injuries in males were traffic accidents and violence, and for females were fall, poisoning, scorpion and snake bites (P<0.001). There was significant difference in the place that accident happened for male and female (P<0.001). Conclusion: Accidents among elderly are of special importance for a number of reasons include: age related changes, preexisting conditions and drug consumption. Prevention education and implementation of safety measures at home and at community places would help reduce injuries related accidents and should be taken into consideration.